Pendampingan UMKM Kuliner di Mahavihara Mojopahit Desa Bejijong Trowulan - Efferin, Sujoko; Prianka, Dian; Yunita, Oeke (LPPM Universitas Narotama, 2024)
Current culinary business trends have a direct relationship to the culinary sector's favorable prospects and opportunities. Culinary MSMEs in Mahavihara Mojopahit, Bejijong Village, Trowulan need to expand their customer base beyond tourists to the Mahavihara Mojopahit tourist area. This circumstance necessitates a more proactive marketing strategy, namely a digital marketing strategy. Assistance for MSMEs begins with a preparation period that includes Focus Group Discussions and comparative studies of culinary tourism centers (SWK) that have successfully implemented digital marketing strategies. Furthermore, assistance is provided through stepwise training in digital content production, customer engagement, and operational management. This MSME assistance can strengthen the knowledge and skills of MSME partners in digital.marketing.